2020
DOI: 10.18231/j.ijirm.2020.060
|View full text |Cite
|
Sign up to set email alerts
|

An understanding of interlink of Vitamin D with Tuberculosis- A cross-sectional study

Abstract: Tuberculosis (TB) is the most prevalent health disorder in developing nations and is linked with decreased immunity. Vitamin D is one of the most important vitamins required to boost immune response as it is required to maintain innate immune response via its actions on TLRs and macrophages. Risk of Tuberculosis has been associated with decrease level of vitamin D in serum in various studies. Despite of these studies some discrepancies have been shown in different studies conducted in different regions which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
3
0
0
Order By: Relevance
“…The application of the Mann-Whitney test indicated a significant statistical difference (p-value of 0.029) between the TB cases and the non-TB populations. Like our study, other studies also revealed low vitamin D levels in the TB group compared with the control group [13,14,20,[22][23][24].…”
Section: Mean Value Of Vitamin D In the Cases And Controlssupporting
confidence: 84%
See 2 more Smart Citations
“…The application of the Mann-Whitney test indicated a significant statistical difference (p-value of 0.029) between the TB cases and the non-TB populations. Like our study, other studies also revealed low vitamin D levels in the TB group compared with the control group [13,14,20,[22][23][24].…”
Section: Mean Value Of Vitamin D In the Cases And Controlssupporting
confidence: 84%
“…Like our study, other studies showed vitamin D deficiency more in cases than controls [19][20][21][22]. In a few studies, vitamin D deficiency was seen only in cases but none in controls [13,14,23,24].…”
Section: Prevalence Of Vitamin D Deficiency In the Cases And Controlssupporting
confidence: 79%
See 1 more Smart Citation